2018
DOI: 10.1093/nar/gky1150
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence elements required for partitioning competence of theSaccharomyces cerevisiae2-micron plasmidSTBlocus

Abstract: Equal partitioning of the multi-copy yeast 2-micron plasmid requires association of plasmid proteins Rep1 and Rep2 with tandem repeats at the plasmid STB locus. To identify sequence elements required for these associations we generated synthetic versions of a 63-bp section of STB, encompassing one repeat. A single copy of this sequence was sufficient for Rep protein association in vivo, while two directly arrayed copies provided partitioning function to a plasmid lacking all other 2-micron sequences. Partition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The partitioning system [57], comprised of the plasmid-coded Rep1 and Rep2 proteins together with a cis -acting locus STB , promotes nearly equal segregation of plasmid molecules duplicated by the host replication machinery into mother and daughter cells. Current evidence is consistent with a ‘hitchhiking model’ in which the plasmid utilizes chromosomes as a vehicle for segregation by physically associating with them [811].…”
Section: Introductionmentioning
confidence: 99%
“…The partitioning system [57], comprised of the plasmid-coded Rep1 and Rep2 proteins together with a cis -acting locus STB , promotes nearly equal segregation of plasmid molecules duplicated by the host replication machinery into mother and daughter cells. Current evidence is consistent with a ‘hitchhiking model’ in which the plasmid utilizes chromosomes as a vehicle for segregation by physically associating with them [811].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these previous studies described above (Hartley and Donelson, 1980;Jayaram et al, 1983;Rizvi et al, 2018;McQuaid et al, 2019), we identified a new insertion site between the REP1 promoter and RAF1 promoter (Supplementary Figure 1B). The pBR322ori, KanMX selection marker gene, and three endonuclease sites XhoI/PmeI/NotI were inserted in this site.…”
Section: Introductionmentioning
confidence: 85%
“…Many researchers took advantage of the high PCN and stable inheritance of the 2µ plasmid to directly transform 2µ plasmid as an expression tool. Ludwig et al selected the HPAI restriction site of STB as the insertion site (Ludwig and Bruschi, 1991), but the loss of STB led to a high loss rate of the plasmid (Murray and Szostak, 1983;McQuaid et al, 2019). Misumi et al (2018) inserted the yeast promoter, terminator, and nutritional deficiency marker gene leu2 between RAF1 and STB and called this plasmid YHp.…”
Section: Introductionmentioning
confidence: 99%
“…The TRP1- tagged ARS plasmids pTRP1/ARS and pTRP1/ARS/lexAop8 were created by replacing a 600-bp BamHI/NruI fragment in the plasmid pYR7 ( 64 ) with a BamHI/ScaI fragment encoding the UASΔGAL1 promoter region, obtained from the one-hybrid vector pJL638 ( 65 ) or amplified from the genome of the one-hybrid reporter yeast strain CT/MD/3a ( 66 ), respectively. In the latter, two copies of a 78-bp oligonucleotide inserted at the cloning site in pJL638, each encoding two colE1 (overlapping) operator sequences, provide eight tandem LexA binding sites (lexA op8 ) in the pTRP1/ARS/lexAop8 plasmid ( 67 ).…”
Section: Methodsmentioning
confidence: 99%